Blending Process of Cellulose Nanofiber /Polyvin y l Alco hol (NFC/PVA) For Paper Coating Application - Ni Made Sudri; Aniek Sri Handayani; Ratnawati; Athanasia Amanda Septevani; Mutiara Eka Puspita; Yuli Amalia Husnil; Yalun Arifin; Annisa Nurul Syabila; Muhamad Rofi Zul Qois (Jurnal Sains Materi Indonesia, 2023)
This paper describes how to make films using polyvinyl alcohol (PVA) and nanofiber cellulose (NFC). In this study, different NFC and PVA ratios were varied. To achieve ideal condition during the film making process, several characteristics, including as density and viscosity, have been investigated using Taguchi method. The results showed two main outcomes. To obtain optimal viscosity, the NFC/PVA ratio factor is 5/95, the volume/volume ratio is 10%, and the sonication time is 7 minutes. For optimal density, several conditions can be used, including a NFC/PVA ratio of 10/90, volume/volume ratio of 3%, and a sonication time of 5 minutes. The experimental results confirmed the average viscosity response of 129.99 ± 13.33 and the S/N ratio of -42.64 ± 0.56. The experimental results of the Taguchi method were -42.64 ± 0.56 and the S/N ratio was -42.92 ± 0.67. Meanwhile, the response data for the Taguchi methodal density averaged at 1.042 ± 0.013 and the S/N ratio was -0.365 ± 0.104. For the results of the experimental condition were 1.126 ± 0.015 and the S/N ratio of -1.031 ± 0.124.From these data, it can be concluded that there is an increase in the average and variability which indicates that the blending process is getting better with the use of NFC.